An investigation of the use of information and communication technology in secondary schools: Teachers’ voices - Saputra, Dwi Bayu; Puspa, Adelia; Haryana, Lia; Muswari, Reci (English Learning Innovation, 2024)
Despite the fact that there has been a lot of research on online learning and the use of technology, researchers have paid very little attention to the use of information and communication technology after the COVID-19 pandemic, particularly on the perceptions of teachers who teach at the middle and high school levels. As a result, this study aims to analyze teacher perspectives on the use of technology, information, and communication, particularly in English subjects. A mixed methods technique will be applied in this investigation. To acquire a deeper understanding of middle and high school teachers' impressions of using ICT in English language learning, researchers utilize quantitative data from surveys and qualitative data from free-form writing. First, the questionnaire will be distributed to teachers using the Snowball method. After all the data from the questionnaire is received, the researcher will distribute some questions concerning the challenges, suggestions, and teachers' opinions on using ICT in English classes to obtain more in-depth information. The findings of this study show that teachers have a positive attitude toward using ICT, particularly in the teaching and learning process. One of the most important considerations is that incorporating technology into the teaching and learning process may improve the classroom atmosphere and engage students in the teaching and learning process. Future studies can explore teachers' perceptions using qualitative methods so that the data obtained will be deeper and can enrich the knowledge related to ICT use after the COVID-19 pandemic.